2019
DOI: 10.1177/0886260519827666
|View full text |Cite
|
Sign up to set email alerts
|

Dark Triad Traits and Perceptions of Sexual Harassment

Abstract: Those high on Dark Triad traits (narcissism, Machiavellianism, primary and secondary psychopathy) are more likely to engage in sexual harassment and less likely to empathize with others. Few studies have, however, considered the impact of Dark Triad traits on perceptions of sexually aggressive behavior performed by others. The present study investigated the relationship between Dark Triad traits and perceptions of sexual harassment. Heterosexual women ( N = 142) aged 18 to 50 years ( M = 20.86, SD = 5.62) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
(59 reference statements)
0
26
0
1
Order By: Relevance
“…Another model that has been proposed to account for the characteristics of sexual aggressors is the “Dark Triad.” Jones and Paulhus (2011) defined this model as including three components: (1) Psychopathy : Characterized by callousness, impulsive thrill‐seeking, and criminal behavior (e.g., “People who mess with me always regret it”); (2) Machiavellianism : Marked by strategic manipulation (e.g., “There's a sucker born every minute”); and (3) Narcissism : Associated with grandiosity, egocentrism, and sense of personal entitlement (e.g., “I insist on getting the respect that I deserve”). Although there have been recent criticisms of this model (e.g., Miller et al, 2019), it continues to be widely used generally and specifically in the area of sexual aggression (e.g., Brewer et al, 2019). This model overlaps in some ways with Confluence Model in the Narcissism aspect and obviously with Psychopathy in that both include this factor, but it is unique in adding the Machiavellianism component (Jonason et al, 2017).…”
Section: Overviewmentioning
confidence: 99%
“…Another model that has been proposed to account for the characteristics of sexual aggressors is the “Dark Triad.” Jones and Paulhus (2011) defined this model as including three components: (1) Psychopathy : Characterized by callousness, impulsive thrill‐seeking, and criminal behavior (e.g., “People who mess with me always regret it”); (2) Machiavellianism : Marked by strategic manipulation (e.g., “There's a sucker born every minute”); and (3) Narcissism : Associated with grandiosity, egocentrism, and sense of personal entitlement (e.g., “I insist on getting the respect that I deserve”). Although there have been recent criticisms of this model (e.g., Miller et al, 2019), it continues to be widely used generally and specifically in the area of sexual aggression (e.g., Brewer et al, 2019). This model overlaps in some ways with Confluence Model in the Narcissism aspect and obviously with Psychopathy in that both include this factor, but it is unique in adding the Machiavellianism component (Jonason et al, 2017).…”
Section: Overviewmentioning
confidence: 99%
“…With regard to coercive behavior, both psychopathy (Jones & Olderbak, 2014;Muñoz et al, 2011) and narcissism (Blinkhorn et al, 2015) predict the self-reported use of coercion after rejection of sexual advances. While some studies highlight the relationship between primary psychopathy (i.e., cold, callous, interpersonal-affective) and sexual coercion (Brewer et al, 2019;Muñoz et al, 2011), others suggest that aspects of secondary psychopathy (i.e., impulsive, antisocial behavior) predict coercion reflecting an increased motivation to feel powerful (Hoffmann & Verona, 2019). Indeed, there may be many motivations, cognitions, and strategies that connect the Dark Triad to sexual coercion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, literature has supported links between Dark Triad traits and sexual harassment behaviours (e.g. [37][38][39]). For example, some studies evidence that psychopathy and narcissism are related to the perpetration of aggressive sexual behaviour (see [39] for a review).…”
Section: The Dark Triad and Sexual Cyberbullying Behaviourmentioning
confidence: 99%
“…[37][38][39]). For example, some studies evidence that psychopathy and narcissism are related to the perpetration of aggressive sexual behaviour (see [39] for a review). Within sexual harassment framework, sexual cyberbullying is a relatively new issue to which literature is devoting greater focus.…”
Section: The Dark Triad and Sexual Cyberbullying Behaviourmentioning
confidence: 99%